Interpretasi Ziarah pada Makam Mbah Priuk (Sebuah Kajian Etnografi) - syamhari syamhari (Rihlah : Jurnal Sejarah dan Kebudayaan, 2014)
Interpretation of visiting Mbah Priuk grave. This research used descriptive analysis in etnographe methode. This research result has found that visiting grave is a tradition is growth as naturally whether through tradition in every families and then tradition as generally. When relationship nowdays with human life is cannot be separated with habitual area, tradition, culture and truth. Visiting grave is part of the tradition that be continued has been built by people before them. About the meaning and rules of visiting grave, every group’s societies own by themselves. But Mbah Priuk grave has been found the same rules of visiting grave without they took their tradition of visiting that make habitual in every vellages. There are religion values found  strong in themselves that all expulsions, sacrifices whether materials and non-materials are found will get the blessing from Allah becouse they have made the good thing.